Production of biodiesel from safflower oil - Behcet, Rasim; Aydin, Selman; Ilkilic, Cumali (Sila Science, 2011)
Safflower seeds oil transesterification was studied with the purpose of biodiesel production. Transesterification reactions were carried out for 2 hours at 55 degrees C using safflower oil, methanol, and sodium hydroxide as catalyst. In order to determine the best conditions for biodiesel production, a series of experiments were carried out, using methanol/safflower oil molar ratios between 3 and 5 and catalyst/safflower oil weight ratios between 0.6% and 1.0%. Results showed that 0.4% of NaOH/safflower oil and 20% of methanol/safflower oil in weight gave the best biodiesel. Thus safflower oil biodiesel was produced. The fuel properties of safflower biodiesel so obtained complied with the requirements of both the American and European standards for biodiesel. This implies safflower oil obtained biodiesel can be used as an alternative diesel fuel.
Keywords: Diesel engine; Biodiesel; Alternative fuel; Safflower oil